Positioning the Academic Library Within the University 2021
DOI: 10.4324/9781003139072-2
|View full text |Cite
|
Sign up to set email alerts
|

Positioning the Academic Library within the Institution: A Literature Review

Abstract: A strong position in the institution is vital for any academic library and affects its recognition, resourcing and prospects. Higher education institutions are experiencing radical change, driven by greater accountability, stronger competition and increased internationalisation. They prioritise student success, competitive research and global reputation. This has significant implications for library strategy, space, structures, partnerships and identity. Strategic responses include refocusing from collections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Librarians lacked the knowledge of which technology to implement in their libraries; otherwise, how can they implement something they did not know exists? Furthermore, other studies reported a lack of awareness hindered the implementation of digital transformation technologies such as RDM (Cox, 2019; Tang and Hu, 2019), LMS (Aregbesola et al , 2019; Buwule and Ponelis, 2017; Olatunji et al , 2020) and cloud computing (Meher and Maharana, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Librarians lacked the knowledge of which technology to implement in their libraries; otherwise, how can they implement something they did not know exists? Furthermore, other studies reported a lack of awareness hindered the implementation of digital transformation technologies such as RDM (Cox, 2019; Tang and Hu, 2019), LMS (Aregbesola et al , 2019; Buwule and Ponelis, 2017; Olatunji et al , 2020) and cloud computing (Meher and Maharana, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To remain relevant, they must respond to current trends and anticipate users’ future needs, and at the same time develop innovative initiatives to address those needs. University libraries in the 21st century engage in digital transformation by adopting technological trends, such as implementing innovations in scholarly communication, creating spaces for collaborative and creative learning, increasing attention to research data management (RDM), preservation and curation, promotion and use of mobile technologies and social media, acquisition of electronic resources and integration of ICTs (Anuradha, 2018; Cox, 2019; Ellis et al , 2014; Jain and Akakandelwa, 2016; Hamad et al , 2018). In addition, university libraries have implemented cloud computing technologies making them “greener” (Enefu et al , 2015) and smarter (Wada, 2018), integrated library management systems (ILMS) to enhance operational efficiency by integrating library functions such as acquisition, cataloguing, management, circulation and the online public access catalogue (OPAC) (Komolafe-Opadeji and Ojo, 2019; Ponelis and Adoma, 2018; Aregbesola et al , 2019) and discovery tools (Jantzi et al , 2016; Stukalova and Guskov, 2016).…”
Section: Introductionmentioning
confidence: 99%